Embodied GHG Emissions of Wooden Buildings—Challenges of Biogenic Carbon Accounting in Current LCA Methods - Andersen, C. E.; Rasmussen, F. N.; Habert, G.; Birgisdóttir, H. (Frontiers in Built Environment, 2021)
Buildings play a vital role in reaching the targets stated by the Intergovernmental Panel on Climate Change to limit global warming to 1.5 degrees. Increasing the use of wood in construction is a proposed upcoming strategy to reduce the embodied greenhouse gas emissions of buildings. This study examines existing life cycle assessments of wooden buildings. The aim is to investigate embodied greenhouse gas emission results reported, as well as methodological approaches applied in existing literature. The study applies the protocol for Systematic Literature Reviews and finds 79 relevant papers. From the final sample, the study analyses 226 different scenarios in-depth in terms of embodied emissions, life cycle assessment method, life cycle inventory modelling and biogenic carbon approach. The analysis shows that the average reported values of embodied greenhouse gas emissions of wooden buildings are one-third to half of the embodied emissions reported from buildings in general. Additionally, from the analysis of the final sample we find that the majority of wooden building life cycle assessments apply similar methods and often leave out biogenic carbon from the assessment or simply do not declare it. This implies that the focus on variability in the different methods applied in wooden building life cycle assessments needs to be increased to establish the relationship between methodological choices and embodied emissions of wooden buildings. Further, transparency and conformity in biogenic carbon accounting in life cycle assessments is essential to enhance comparability between life cycle assessment studies and to avoid distortions in embodied GHG emission results.